Prevalence of Mental Disorders in a German Kidney Transplant Population: Results of a KTx360°-Substudy - Birkefeld, Katrin; Bauer-Hohmann, Maximilian; Klewitz, Felix; Kyaw Tha Tun, Eva Marie; Tegtbur, Uwe; Pape, Lars; Schiffer, Lena; Schiffer, Mario; de Zwaan, Martina; Nöhre, Mariel (Journal of Clinical Psychology in Medical Settings, 2022)
In patients after kidney transplantation (KTx) an increased rate of affective and anxiety disorders has been observed. Repeatedly, a relationship between mental health issues and increased morbidity and mortality in KTx recipients has been reported. However, information on the prevalence of mental disorders in KTx patients is scarce. As part of the structured multimodal follow-up program (KTx360°), mental disorders were examined in 726 patients after KTx through structured diagnostic interviews using the Mini-DIPS Open Access. Overall, 27.5% had a current and 49.2% a lifetime mental disorder. Only 14.5% with a current mental disorder reported to be in treatment. Affected patients were younger, more often female, reported more symptoms of anxiety and depression and less perceived social support. While comparable to the rate in general population samples, the prevalence of mental disorders should attract attention. The low treatment rate requires an improved identification of afflicted patients and provision of specialist treatment. ISRCTN registry, https://doi.org/10.1186/ISRCTN29416382, date of registry: 03.05.2017.
CRIS-Team Scopus Importer:2022-03-04
Keywords: Kidney transplantation; Mental comorbidity; Mental health; Psychotherapeutic treatment; Renal transplantation